Retrospective Analysis of Toxicity Profiles of Two Platinum-Based Salvage Regimens in Relapsed/Refractory Lymphoma: DHAP versus ESHAP - (:unkn) unknown (AKAD DOKTORLAR YAYINEVI, 2016)
Platinum- or ifosfamide-based salvage therapies such as DHAP, ICE and ESHAP are frequently used regimens in relapsed/refractory lymphomas. The most important adverse effect of salvage therapies is hematologic toxicity. The aim of this study to compare the hematologic and non-hematological toxicity profiles of two different platinum-based salvage chemotherapy regimens used in relapsed/refractory lymphoma. We evaluated 51 patients with HL and NHL who were treated with DHAP and ESHAP regimens (n=18 for DHAP and n=33 for ESHAP) between January 2000 and July 2010. These patients had received a total of 153 cycles (62 DHAP and 91 ESHAP). Data were retrospectively collected from patients' chart records and electronic patient inventory. Receiving DHAP regimen was found to be an independent risk factor for renal toxicity (Odds ratio [OR]=23.6, p=0.03) and independent predictor of platelet transfusion requirement (OR: 7.55, p=0.03). Overall response was significantly higher in DHAP group (86.7% vs 48.3%, p=0.03) but there was no significant difference between two groups in terms of median survival. DHAP regimen is associated with higher response rates but has no survival advantage. Although the hematologic and non-hematologic toxicity profiles were similar, increased risk for renal toxicity and platelet transfusion requirement should be considered for patients planned to receive DHAP regimen.
Keywords: Lymphoma; Salvage chemotherapy; Toxicity; HIGH-DOSE CYTARABINE; B-CELL LYMPHOMA; NON-HODGKINS-LYMPHOMA; AGGRESSIVE LYMPHOMA; ICE IFOSFAMIDE; FOLLOW-UP; PHASE-II; ARA-C; DEXAMETHASONE; CHEMOTHERAPY